Jika (fo g) (x) = 2x-3 / 6x-9 dan g (x) = 2x + 4 maka f(x) =…

Jika (fo g) (x) = 2x-3 / 6x-9 dan g (x) = 2x + 4 maka f(x) =…

 

jawaban yang benar adalah f(x) = (x – 7)/(3x – 21). Pembahasan: (f o g)(x) = f(g(x)) sehingga (f o g)(x) = (2x – 3)/(6x – 9) f(2x + 4) = (2x – 3)/(6x – 9) diperoleh y = 2x + 4 y – 4 = 2x (y – 4)/2 = x Oleh karena itu f(x) = (2((x – 4)/2) – 3)/(6((x – 4)/2) – 9) f(x) = (x – 4 – 3)/(3(x – 4) – 9) f(x) = (x – 7)/(3x – 12 – 9) f(x) = (x – 7)/(3x – 21) Dengan demikian, diperoleh f(x) = (x – 7)/(3x – 21).